Sub-national fiscal policy under cooperative and non-cooperative models (2016)
This article presents a comparative analysis of the optimal fiscal response to shocks in the sub-national public sector in cooperative and non-cooperative models. The analysis is undertaken by comparing models that assume idiosyncratic demandside shocks and sub-national autonomy to collect taxes, with models that assume that the central government collects the taxes of the whole country and redistributesthem across regions. Results show that under symmetrical conditions, the non-cooperative solution may result in greater stabilization and lower sub-national public expenditure than the cooperative solution. However, if regional asymmetries are introduced into the model, results may be reversed.